(untitled) (Gaceta Técnica, 2015)
The competency-based approach during teaching, leads to consider the work of teachers in relation to planning strategies that contribute to educational development. In this sense, the present study was developed under the quantitative paradigm and its purpose was to determine whether program faculty of civil engineering at Lisandro Alvarado University, reflected in their teaching plans, strategies based on competence approach to adjust each program subjects to the recommended profile by the Central Commission for Curriculum. To collect this information a questionnaire consisting of 23 items, was applied to a sample of 45 teachers, who accounted for 33% of the study population. The results of this study evidenced that teachers despite having received guidelines for the redesign of the programs of the subjects managed under the competency-based approach, have deficiencies in the use of teaching strategies based on this approach, to ensure the formation of a comprehensive professional, social and environmental sensitive, as stipulated in the new curriculum driven institution